Magnetic powder and shaping method and application thereof
By heat treatment, ball milling and etching treatment of mechanically broken ferrosilicon aluminum magnetic powder, the problem of difficult removal of sharp angles and burrs in the prior art is solved, and the density of the magnetic core and the DC superposition characteristics are improved.
Patent Information
- Application Number
- CN202310829274.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to effectively remove sharp corners and burrs of mechanically broken ferrosilicon aluminum magnetic powder under low cost conditions, resulting in poor magnetic properties and moldability of the magnetic core.
By adopting steps including first heat treatment, ball milling and acid etching treatment, the sharp corners and burrs of the magnetic powder are removed by improving the processing characteristics and morphology of the magnetic powder, and finally repairing the morphology and microscopic defects through the second heat treatment to form a high spherical shape. Smooth surface magnetic powder.
It significantly improves the density, loss and DC superposition characteristics of the magnetic core, and improves the shaping effect of magnetic powder.
Smart Images

Figure BDA0004326356610000091 
Figure BDA0004326356610000101 
Figure BDA0004326356610000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials and relates to magnetic powder and a shaping method and application thereof. Background Art
[0002] Metallic soft magnetic composites (SMC) have higher saturation magnetic induction intensity than traditional ferrites, which is conducive to the miniaturization of devices. At the same time, there is a natural gas gap inside the metal soft magnetic composite material, which has good DC superposition characteristics and is widely used in transformers, inductors and other devices. Iron-silicon-aluminum-based soft magnetic composites have the advantages of low loss and high magnetic permeability. They are the most widely used and most demanded type of metal soft magnetic composite materials.
[0003] The magnetic powder of Sendust-based soft magnetic composite materials is usually divided into the following three types: gas atomized powder, water atomized powder and mechanically crushed powder. Among them, gas atomized magnetic powder has the advantages of high sphericity and low oxygen content, and is the best choice for preparing high-performance Sendust-based soft magnetic composite materials. However, the oxygen content of water atomized magnetic powder is relatively high, the sphericity is slightly poor, and the loss is relatively high; mechanically crushed powder is usually irregular in shape, with obvious sharp corners, and the coating is easily punctured during the pressing process. At the same time, the formability is poor, resulting in poor final core loss, DC superposition and other performance. However, compared with gas atomized magnetic powder, the process cost of mechanically crushed Sendust-based magnetic powder is lower and the powder yield is higher. Therefore, it is of great significance to improve the morphology and formability of mechanically crushed Sendust-based magnetic powder and thus improve the performance of soft magnetic composite materials.
[0004] However, the current prior art generally directly uses a shaping device to shape the morphology of magnetic powder. For example, CN105710378A discloses a method for shaping quasi-spherical metal soft magnetic alloy powder. In this method, the raw materials of the metal soft magnetic alloy are weighed and proportioned according to a weight ratio, medium-frequency induction smelting is adopted, and then the molten alloy is prepared into an alloy casting strip through a thin strip continuous casting process: the alloy casting strip is placed in a crushing device and crushed into granular powder under inert gas protection conditions; the crushed powder is placed in a shaping processing device for shaping treatment to obtain a regularly shaped quasi-spherical powder, wherein the shaping processing device is at least one of powder spheroidizing equipment such as a powder spheroidizer, an air flow mill and a Hami tower; when the above-mentioned shaping device is used for shaping, the device cost is relatively high, and it is impossible to efficiently remove fine burrs and sharp corners on the surface of the particles under low-cost conditions.
[0005] Based on the above research, it is necessary to provide a method for shaping magnetic powder, which can remove the sharp corners of the magnetic powder and optimize the morphology of the magnetic powder at a low cost, thereby improving the magnetic properties and formability of the magnetic core. Summary of the invention
[0006] The purpose of the present invention is to provide a magnetic powder and a shaping method and application thereof, and in particular to a mechanically crushed sendustine magnetic powder and a shaping method and application thereof. The shaping method can effectively remove burrs and sharp corners caused by mechanical crushing of the magnetic powder by improving the processing characteristics of the magnetic powder, ball milling shaping and micro-repair, and finally obtain magnetic powder with high sphericity, smooth surface and no sharp corners, thereby effectively improving the density, loss and DC superposition characteristics of the magnetic core.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for shaping magnetic powder, the shaping method comprising the following steps:
[0009] (1) subjecting the magnetic powder to a first heat treatment and ball milling in sequence to obtain ball-milled magnetic powder;
[0010] (2) subjecting the ball-milled magnetic powder of step (1) to acid etching and a second heat treatment in sequence to complete shaping and obtain shaped magnetic powder.
[0011] The present invention first performs a first heat treatment on the magnetic powder to improve the processing characteristics of the magnetic powder, thereby facilitating subsequent processing, and then performs a ball milling shaping treatment on the magnetic powder to obtain initially shaped magnetic powder, and then performs an acid etching treatment and a second heat treatment to further repair the morphology and microscopic defects of the magnetic powder to finally obtain the shaped magnetic powder. After the shaped magnetic powder is pressed into a magnetic core, the density, loss and DC superposition characteristics of the magnetic core can be significantly improved.
[0012] Moreover, since the functions of the various steps of the present invention are different and there is a synergistic effect between the steps, the processing sequence of the present invention is to perform a first heat treatment, ball milling, acid etching and a second heat treatment in sequence. Changes in the processing sequence will affect the shaping results. For example, since a small amount of burrs will be formed on the surface of the magnetic powder during the ball milling shaping process, the present invention first performs ball milling and then performs acid etching to achieve surface modification of the magnetic powder, remove the burrs on the surface of the magnetic powder, and further improve the morphology of the magnetic powder.
[0013] Preferably, the temperature of the first heat treatment in step (1) is 800-850°C, for example, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C, and the holding time is 2-4h, for example, 2h, 3h or 4h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, the cooling rate of the first heat treatment in step (1) is 150-200°C / h, for example, 150°C / h, 160°C / h, 170°C / h, 180°C / h, 190°C / h or 200°C / h, and the terminal temperature of the cooling is 20-35°C, for example, 20°C, 25°C, 30°C or 35°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0015] Since the first heat treatment of the present invention is used to improve the processing characteristics of the mechanically crushed magnetic powder, the temperature and cooling rate of the first heat treatment will affect the improvement effect, thereby affecting the subsequent shaping effect.
[0016] Preferably, the first heat treatment in step (1) is carried out under vacuum conditions, or in a protective gas, wherein the protective gas comprises any one of hydrogen, nitrogen or argon, or a combination of at least two of them.
[0017] Preferably, the magnetic powder in step (1) comprises mechanically crushed magnetic powder.
[0018] Since the magnetic powder after mechanical crushing has obvious sharp corners, the coating layer is easily punctured during the pressing process. The shaping method of the present invention is suitable for the shaping of mechanically crushed magnetic powder.
[0019] Preferably, the magnetic powder in step (1) comprises mechanically crushed Sendust magnetic powder.
[0020] The sendust magnetic powder of the present invention comprises Si: 9-10%, Al: 5-6%, and the rest is Fe in weight percentage. The particle size of the magnetic powder is -200 mesh, wherein -200 mesh refers to the magnetic powder passing through a 200-mesh sieve.
[0021] Preferably, during the ball milling in step (1), a grinding aid and grinding balls are added, and after the ball milling, the grinding aid and grinding balls are removed to obtain ball-milled magnetic powder.
[0022] Preferably, the method of removing the grinding aid comprises magnetic separation, and the method of removing the grinding balls comprises screening.
[0023] Preferably, the grinding aid comprises silica.
[0024] Preferably, the average particle size of the silicon dioxide is 1-4 μm, for example, 1 μm, 2 μm, 3 μm or 4 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 2-3 μm.
[0025] Preferably, the amount of the grinding aid is 0.8-2wt% of the weight of the magnetic powder after the first heat treatment, for example, it can be 0.8wt%, 1.0wt%, 1.5wt% or 2wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] The addition of the grinding aid of the present invention can avoid the agglomeration and cold welding between the sendust magnetic powders, and is also conducive to removing sharp corners; in addition, the addition amount of the grinding aid and the selection of the particle size will affect the ball milling effect, thereby affecting the performance of the obtained magnetic core.
[0027] Preferably, the mass ratio of the grinding balls to the magnetic powder after the first heat treatment is (3-5):1, for example, 3:1, 4:1 or 5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the material of the grinding balls includes zirconium oxide.
[0029] Preferably, the grinding balls include first grinding balls with a diameter of 0.5-1.5 mm, such as 0.5 mm, 1.0 mm or 1.5 mm, and second grinding balls with a diameter of 2.5-3.5 mm, such as 2.5 mm, 3 mm or 3.5 mm, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the mass ratio of the first grinding ball to the second grinding ball is (1.5-3):1, for example, 1.5:1, 2:1, 2.5:1 or 3:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] The material, size, combination and ball-to-material ratio of the grinding balls of the present invention affect the shaping effect. The grinding ball material needs to have high hardness and wear resistance. If the grinding ball size is too small, the efficiency is too low and the energy is insufficient to eliminate the sharp corners. If the grinding ball size is too large, the impact energy is too high and the magnetic powder is more likely to break and cannot be effectively shaped. If the ball-to-material ratio is too small, the efficiency is low. If the ball-to-material ratio is too large, the ball milling energy is too high, the magnetic powder will break and the shaping effect will be poor.
[0032] The ball mill of the present invention is a low-energy ball mill, preferably a rolling ball mill.
[0033] Preferably, the mass concentration of the acid solution used for the acid etching in step (2) is 3.5-6.5%, for example, 3.6%, 4.5%, 5.5% or 6.5%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the acid etching time in step (2) is 10-30 seconds, for example, 10 seconds, 20 seconds or 30 seconds, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] During the ball milling shaping process of the present invention, a small amount of burrs will be formed on the surface of the magnetic powder. The acid etching treatment is used to remove the burrs on the surface of the magnetic powder and further improve the surface of the magnetic powder. In addition, if the concentration of the acid solution is too low or the time is too short, the deburring effect will be poor. If the concentration of the acid solution is too high or the etching time is too long, excessive etching will occur, affecting the loss performance of the magnetic core. Therefore, the acid concentration and etching time should be controlled within a certain range.
[0036] Preferably, after the acid etching in step (2), cleaning is performed first and then a second heat treatment is performed.
[0037] Preferably, the cleaning solution used for the cleaning includes distilled water and anhydrous ethanol.
[0038] The cleaning of the present invention comprises firstly washing twice with distilled water to remove excess dilute hydrochloric acid and iron salt, and then washing three times with anhydrous ethanol to remove excess water remaining on the surface of the magnetic powder to prevent oxidation of the surface of the magnetic powder.
[0039] Preferably, the temperature of the second heat treatment in step (2) is 780-830°C, for example, 780°C, 790°C, 800°C, 810°C, 820°C or 830°C, and the holding time is 3-5h, for example, 3h, 4h or 5h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the second heat treatment in step (2) is performed in a reducing atmosphere, wherein the reducing atmosphere includes hydrogen and a mixed gas of hydrogen and nitrogen.
[0041] The second heat treatment of the present invention aims to remove the stress inside the magnetic powder after the shaping process and repair the crystal structure. The use of a reducing atmosphere can remove the oxygen adsorbed on the surface of the magnetic powder during the shaping process, which is beneficial to improving the soft magnetic properties of the magnetic powder.
[0042] As a preferred technical solution of the shaping method of the present invention, the shaping method comprises the following steps:
[0043] (1) subjecting the magnetic powder to a first heat treatment at a temperature of 800-850° C. for 2-4 hours under vacuum conditions or in a protective gas, and then cooling the temperature to 20-35° C. at a cooling rate of 150-200° C. / h to obtain magnetic powder after the first heat treatment;
[0044] The magnetic powder includes mechanically crushed sendust magnetic powder, and the protective gas includes any one of hydrogen, nitrogen or argon, or a combination of at least two of them;
[0045] (2) ball-milling the grinding aid, grinding balls and the magnetic powder after the first heat treatment in step (1), then removing the grinding aid by magnetic separation, and removing the grinding balls by screening to obtain ball-milled magnetic powder;
[0046] The amount of the grinding aid is 0.8-2wt% of the weight of the magnetic powder after the first heat treatment, and the mass ratio of the grinding ball to the magnetic powder after the first heat treatment is (3-5):1;
[0047] The grinding aid is silicon dioxide with an average particle size of 2-3 μm, the grinding balls include first grinding balls with a diameter of 0.5-1.5 mm and second grinding balls with a diameter of 2.5-3.5 mm, and the mass ratio of the first grinding balls to the second grinding balls is (1.5-3):1;
[0048] (3) etching the ball-milled magnetic powder in step (2) in an acid solution having a mass concentration of 3.5-6.5% for 10-30 seconds, and then washing with distilled water and anhydrous ethanol to obtain acid-etched magnetic powder;
[0049] (4) In a reducing atmosphere, subjecting the acid-etched magnetic powder of step (3) to a second heat treatment at a temperature of 780-830° C. for 3-5 hours to complete shaping and obtain shaped magnetic powder.
[0050] In a second aspect, the present invention provides a magnetic powder, which is shaped by the shaping method described in the first aspect.
[0051] In a third aspect, the present invention provides a magnetic core, comprising the magnetic powder as described in the second aspect.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The present invention first performs a first heat treatment on the magnetic powder to improve the processing characteristics of the magnetic powder, thereby facilitating subsequent processing, and then performs a ball milling shaping treatment on the magnetic powder to obtain initially shaped magnetic powder, and then performs an acid etching treatment and a second heat treatment to further repair the morphology and microscopic defects of the magnetic powder to finally obtain the shaped magnetic powder. After the shaped magnetic powder is pressed into a magnetic core, the density, loss and DC superposition characteristics of the magnetic core can be significantly improved. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0055] Example 1
[0056] This embodiment provides a method for shaping magnetic powder, and the shaping method comprises the following steps:
[0057] (1) subjecting the magnetic powder to a first heat treatment at a temperature of 825° C. for 3 h under vacuum conditions, and then cooling the temperature to 25° C. at a cooling rate of 180° C. / h to obtain magnetic powder after the first heat treatment;
[0058] The magnetic powder is mechanically crushed iron silicon aluminum magnetic powder, which includes Si: 9.4%, Al: 5.8%, and the rest is Fe in weight percentage, and the particle size of the magnetic powder is -200 mesh;
[0059] (2) ball-milling the grinding aid, grinding balls and the magnetic powder after the first heat treatment in step (1) in a rolling ball mill, then removing the grinding aid by magnetic separation, and removing the grinding balls by screening to obtain ball-milled magnetic powder;
[0060] The amount of the grinding aid is 1.5wt% of the weight of the magnetic powder after the first heat treatment, and the mass ratio of the grinding balls to the magnetic powder after the first heat treatment is 4:1;
[0061] The grinding aid is silicon dioxide with an average particle size of 2.5 μm, the grinding ball material includes zirconium oxide, including a first grinding ball with a diameter of 1 mm and a second grinding ball with a diameter of 3 mm, and the mass ratio of the first grinding ball to the second grinding ball is 2:1;
[0062] (3) placing the ball-milled magnetic powder in step (2) into a hydrochloric acid solution with a mass concentration of 5%, stirring rapidly, etching for 18 seconds, then washing twice with distilled water, washing three times with anhydrous ethanol, and drying to obtain acid-etched magnetic powder;
[0063] (4) In a hydrogen atmosphere, the magnetic powder after acid etching in step (3) is subjected to a second heat treatment at a temperature of 800° C. for 3.8 hours to complete the shaping.
[0064] Example 2
[0065] This embodiment provides a method for shaping magnetic powder. The shaping method is the same as that of Embodiment 1 except that the temperature of the first heat treatment in step (1) is 780°C.
[0066] Example 3
[0067] This embodiment provides a method for shaping magnetic powder. The shaping method is the same as that of Embodiment 1 except that the temperature of the first heat treatment in step (1) is 860°C.
[0068] Example 4
[0069] This embodiment provides a method for shaping magnetic powder. The shaping method is the same as that of Embodiment 1 except that the cooling rate of the first heat treatment in step (1) is 130° C. / h.
[0070] Example 5
[0071] This embodiment provides a method for shaping magnetic powder. The shaping method is the same as that of Embodiment 1 except that the cooling rate of the first heat treatment in step (1) is 210° C. / h.
[0072] Comparative Example 1
[0073] This comparative example provides a magnetic powder, which is the magnetic powder that has not been shaped in step (1) of Example 1. The magnetic powder is Sendust magnetic powder, which includes Si: 9-10%, Al: 5-6%, and the rest is Fe in weight percentage, and the particle size of the magnetic powder is -200 mesh.
[0074] Comparative Example 2
[0075] This comparative example provides a method for shaping magnetic powder, which is the same as Example 1 except that the first heat treatment in step (1) is not performed.
[0076] The magnetic powders obtained in Examples 1-5 and Comparative Examples 1-2 were surface passivated with phosphoric acid, and then the passivated magnetic powders were treated with a silane KH500 coupling agent, and then silicone resin was added, dried and granulated, and a zinc stearate release agent was added. The treated magnetic powders were placed in a mold with an outer diameter of 12.7 mm and an inner diameter of 7.6 mm for cold pressing at a pressure of 1700 MPa. After molding, the magnetic rings were placed in an annealing furnace for stress relief annealing in a nitrogen atmosphere at a temperature of 710°C for 2 hours to obtain a magnetic ring with a magnetic permeability of 60±3, and the density, loss and DC superposition characteristics of the magnetic rings were tested.
[0077] The morphology and median particle size (D50) of the magnetic powder obtained in Examples 1-5 and Comparative Examples 1-2, as well as the density ρ, loss Pcv (50kHz, 100mT), magnetic permeability μ, and DC superposition characteristics (100Oe) DC-bias of the magnetic cores are shown in Table 1 below:
[0078] Table 1
[0079]
[0080]
[0081] It can be seen from Table 1 that the magnetic core prepared by the magnetic powder treated by the present invention has better loss and DC superposition characteristics than the mechanically crushed powder. In addition, the first heat treatment and process parameters have a great influence on the morphology of the magnetic powder and the magnetic properties of the magnetic core. The temperature and cooling rate of the first heat treatment are controlled within a certain range, which is conducive to further improving the performance of the magnetic core.
[0082] Example 6
[0083] This embodiment provides a method for shaping magnetic powder, and the shaping method comprises the following steps:
[0084] (1) subjecting the magnetic powder to a first heat treatment at a temperature of 810° C. for 3.8 h under vacuum conditions, and then cooling the temperature to 20° C. at a cooling rate of 155° C. / h to obtain magnetic powder after the first heat treatment;
[0085] The magnetic powder is mechanically crushed iron silicon aluminum magnetic powder, which includes Si: 9.4%, Al: 5.8%, and the rest is Fe in weight percentage, and the particle size of the magnetic powder is -200 mesh;
[0086] (2) ball-milling the grinding aid, grinding balls and the magnetic powder after the first heat treatment in step (1) in a rolling ball mill, then removing the grinding aid by magnetic separation, and removing the grinding balls by screening to obtain ball-milled magnetic powder;
[0087] The amount of the grinding aid is 0.9wt% of the weight of the magnetic powder after the first heat treatment, and the mass ratio of the grinding balls to the magnetic powder after the first heat treatment is 4:1;
[0088] The grinding aid is silicon dioxide with an average particle size of 2.5 μm, the grinding ball material includes zirconium oxide, including a first grinding ball with a diameter of 1 mm and a second grinding ball with a diameter of 3 mm, and the mass ratio of the first grinding ball to the second grinding ball is 2.5:1;
[0089] (3) placing the ball-milled magnetic powder in step (2) into a hydrochloric acid solution having a mass concentration of 6.4%, stirring rapidly, etching for 11 seconds, then washing twice with distilled water, washing three times with anhydrous ethanol, and drying to obtain acid-etched magnetic powder;
[0090] (4) In a hydrogen atmosphere, subjecting the acid-etched magnetic powder of step (3) to a second heat treatment at 785° C. for 4.9 h to complete shaping and obtain shaped magnetic powder.
[0091] Example 7
[0092] This embodiment provides a method for shaping magnetic powder. The shaping method is the same as that of Embodiment 6 except that no grinding aid is added in step (2).
[0093] Example 8
[0094] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 6 except that the average particle size of the grinding aid in step (2) is 5.5 μm.
[0095] Example 9
[0096] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 6 except that the amount of the grinding aid in step (2) is 0.6 wt % of the weight of the magnetic powder after the first heat treatment.
[0097] Example 10
[0098] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 6 except that the amount of the grinding aid in step (2) is 2.2 wt% of the weight of the magnetic powder after the first heat treatment.
[0099] The magnetic powder obtained in Examples 6-10 was surface passivated with phosphoric acid, and then the passivated magnetic powder was treated with a silane KH500 coupling agent, and then an organic silicone resin was added. The powder was dried and granulated, and a zinc stearate release agent was added. The treated magnetic powder was placed in a mold with an outer diameter of 12.7 mm and an inner diameter of 7.6 mm for cold pressing at a pressure of 1700 MPa. The formed magnetic ring was placed in an annealing furnace for stress relief annealing in a nitrogen atmosphere at a temperature of 710°C for 2 hours to obtain a magnetic ring with a magnetic permeability of 60±3, and the density, loss and DC superposition characteristics of the magnetic ring were tested.
[0100] The morphology and median particle size (D50) of the magnetic powder obtained in Examples 6-10, as well as the density ρ, loss Pcv (50kHz, 100mT), magnetic permeability μ, and DC superposition characteristics (100Oe) DC-bias of the magnetic cores are shown in Table 2 below:
[0101] Table 2
[0102]
[0103] It can be seen from Table 2 that the grinding aid can avoid the agglomeration and cold welding between Sendust magnetic powders, and is also helpful in removing sharp corners. The amount and particle size of the grinding aid will affect the performance of the magnetic core.
[0104] Embodiment 11
[0105] This embodiment provides a method for shaping magnetic powder, and the shaping method comprises the following steps:
[0106] (1) subjecting the magnetic powder to a first heat treatment at 845° C. for 2.1 h in an argon atmosphere, and then cooling the temperature to 35° C. at a cooling rate of 195° C. / h to obtain magnetic powder after the first heat treatment;
[0107] The magnetic powder is mechanically crushed iron silicon aluminum magnetic powder, which includes Si: 9.4%, Al: 5.8%, and the rest is Fe in weight percentage, and the particle size of the magnetic powder is -200 mesh;
[0108] (2) ball-milling the grinding aid, grinding balls and the magnetic powder after the first heat treatment in step (1) in a rolling ball mill, then removing the grinding aid by magnetic separation, and removing the grinding balls by screening to obtain ball-milled magnetic powder;
[0109] The amount of the grinding aid is 1.9wt% of the weight of the magnetic powder after the first heat treatment, and the mass ratio of the grinding balls to the magnetic powder after the first heat treatment is 3.8:1;
[0110] The grinding aid is silicon dioxide with an average particle size of 3 μm, the grinding ball material includes zirconium oxide, including a first grinding ball with a diameter of 0.5 mm and a second grinding ball with a diameter of 2.5 mm, and the mass ratio of the first grinding ball to the second grinding ball is 2.2:1;
[0111] (3) placing the ball-milled magnetic powder in step (2) into a hydrochloric acid solution with a mass concentration of 3.6%, stirring rapidly, etching for 28 seconds, then washing twice with distilled water, washing three times with anhydrous ethanol, and drying to obtain acid-etched magnetic powder;
[0112] (4) In a mixture of hydrogen and nitrogen in a volume ratio of 3:1, the magnetic powder after acid etching in step (3) is subjected to a second heat treatment at a temperature of 810° C. for 3.5 h to complete the shaping and obtain the shaped magnetic powder.
[0113] Example 12
[0114] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 11 except that in step (2), the mass ratio of the first grinding ball to the second grinding ball is 1:1.
[0115] Embodiment 13
[0116] This embodiment provides a method for shaping magnetic powder. The shaping method is the same as that of Embodiment 11 except that in step (2), the mass ratio of the first grinding ball to the second grinding ball is 4:1.
[0117] Embodiment 14
[0118] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 11 except that the mass ratio of the total weight of the grinding balls to the mass of the magnetic powder after the first heat treatment in step (2) is 2.8:1.
[0119] Embodiment 15
[0120] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 11 except that the mass ratio of the total weight of the grinding balls to the mass of the magnetic powder after the first heat treatment in step (2) is 5.5:1.
[0121] The magnetic powder obtained in Examples 11-15 was surface passivated with phosphoric acid, and then the passivated magnetic powder was treated with a silane KH500 coupling agent, and then an organic silicone resin was added. The powder was dried and granulated, and a zinc stearate release agent was added. The treated magnetic powder was placed in a mold with an outer diameter of 12.7 mm and an inner diameter of 7.6 mm for cold pressing at a pressure of 1700 MPa. The formed magnetic ring was placed in an annealing furnace for stress relief annealing in a nitrogen atmosphere at a temperature of 710°C for 2 hours to obtain a magnetic ring with a magnetic permeability of 60±3, and the density, loss and DC superposition characteristics of the magnetic ring were tested.
[0122] The morphology and median particle size (D50) of the magnetic powder obtained in Examples 11-15, as well as the density ρ, loss Pcv (50kHz, 100mT), magnetic permeability μ, and DC superposition characteristics (100Oe) DC-bias of the magnetic cores are shown in Table 3 below:
[0123] Table 3
[0124]
[0125]
[0126] It can be seen from Table 3 that the weight ratio of large and small grinding balls and the ball-to-material ratio in ball milling will affect the morphology of magnetic powder and the performance of magnetic core, and it is preferably controlled within a specific range.
[0127] Example 16
[0128] This embodiment provides a method for shaping magnetic powder, and the shaping method comprises the following steps:
[0129] (1) subjecting the magnetic powder to a first heat treatment at 820° C. for 3 h under vacuum conditions or in a protective gas, and then cooling the temperature to 25° C. at a cooling rate of 180° C. / h to obtain magnetic powder after the first heat treatment;
[0130] The magnetic powder is mechanically crushed sendust magnetic powder, which includes Si: 9.4%, Al: 5.8%, and the rest is Fe in weight percentage, and the particle size of the magnetic powder is -200 mesh;
[0131] (2) ball-milling the grinding aid, grinding balls and the magnetic powder after the first heat treatment in step (1) in a rolling ball mill, then removing the grinding aid by magnetic separation, and removing the grinding balls by screening to obtain ball-milled magnetic powder;
[0132] The amount of the grinding aid is 1.6wt% of the weight of the magnetic powder after the first heat treatment, and the mass ratio of the grinding balls to the magnetic powder after the first heat treatment is 4.2:1;
[0133] The grinding aid is silicon dioxide with an average particle size of 2.2 μm, the grinding ball material includes zirconium oxide, including a first grinding ball with a diameter of 1 mm and a second grinding ball with a diameter of 3 mm, and the mass ratio of the first grinding ball to the second grinding ball is 2.5:1;
[0134] (3) placing the ball-milled magnetic powder in step (2) into a hydrochloric acid solution having a mass concentration of 4.5%, stirring rapidly, etching for 20 seconds, then washing twice with distilled water, washing three times with anhydrous ethanol, and drying to obtain acid-etched magnetic powder;
[0135] (4) In a hydrogen atmosphere, subjecting the acid-etched magnetic powder of step (3) to a second heat treatment at 805° C. for 4 h to complete shaping and obtain shaped magnetic powder.
[0136] Embodiment 17
[0137] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 16 except that the mass concentration of the hydrochloric acid solution in step (3) is 3.1%.
[0138] Embodiment 18
[0139] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 16 except that the mass concentration of the hydrochloric acid solution in step (3) is 6.8%.
[0140] Embodiment 19
[0141] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 16 except that the acid etching time in step (3) is 8 seconds.
[0142] Embodiment 20
[0143] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 16 except that the acid etching time in step (3) is 35 seconds.
[0144] Comparative Example 3
[0145] This comparative example provides a method for shaping magnetic powder, which is the same as Example 16 except that the acid etching treatment in step (3) is not performed.
[0146] The magnetic powders obtained in Examples 16-20 and Comparative Example 3 were surface passivated with phosphoric acid, and then the passivated magnetic powders were treated with a silane KH500 coupling agent, and then silicone resin was added. The powders were dried and granulated, and a zinc stearate release agent was added. The treated magnetic powders were placed in a mold with an outer diameter of 12.7 mm and an inner diameter of 7.6 mm for cold pressing at a pressure of 1700 MPa. The formed magnetic rings were placed in an annealing furnace for stress relief annealing in a nitrogen atmosphere at a temperature of 710°C for 2 hours to obtain a magnetic ring with a magnetic permeability of 60±3. The density, loss and DC superposition characteristics of the magnetic rings were tested.
[0147] The morphology and median particle size (D50) of the magnetic powders obtained in Examples 16-20 and Comparative Example 3, as well as the density ρ, loss Pcv (50kHz, 100mT), magnetic permeability μ, and DC superposition characteristics (100Oe) DC-bias of the magnetic cores are shown in Table 4 below:
[0148] Table 4
[0149]
[0150] As shown in Table 4, the acid etching treatment has an important influence on the morphology of magnetic powder and the performance of magnetic core. If the hydrochloric acid concentration is too low or the time is too short, the deburring effect will be poor. If the hydrochloric acid concentration is too high or the etching time is too long, it will lead to excessive etching and affect the loss performance of the magnetic core. Therefore, the hydrochloric acid concentration and etching time should be controlled within a certain range.
[0151] Embodiment 21
[0152] This embodiment provides a method for shaping magnetic powder, and the shaping method comprises the following steps:
[0153] (1) subjecting the magnetic powder to a first heat treatment at 840° C. for 2.5 h in an argon atmosphere, and then cooling the temperature to 25° C. at a cooling rate of 170° C. / h to obtain magnetic powder after the first heat treatment;
[0154] The magnetic powder is mechanically crushed sendust magnetic powder, which includes Si: 9.4%, Al: 5.8%, and the rest is Fe in weight percentage, and the particle size of the magnetic powder is -200 mesh;
[0155] (2) ball-milling the grinding aid, grinding balls and the magnetic powder after the first heat treatment in step (1) in a rolling ball mill, then removing the grinding aid by magnetic separation, and removing the grinding balls by screening to obtain ball-milled magnetic powder;
[0156] The amount of the grinding aid is 1.5wt% of the weight of the magnetic powder after the first heat treatment, and the mass ratio of the grinding balls to the magnetic powder after the first heat treatment is 4:1;
[0157] The grinding aid is silicon dioxide with an average particle size of 2.8 μm, the grinding ball material includes zirconium oxide, including a first grinding ball with a diameter of 1.5 mm and a second grinding ball with a diameter of 3.5 mm, and the mass ratio of the first grinding ball to the second grinding ball is 2.3:1;
[0158] (3) placing the ball-milled magnetic powder in step (2) into a hydrochloric acid solution having a mass concentration of 5%, stirring rapidly, etching for 20 seconds, then washing twice with distilled water, washing three times with anhydrous ethanol, and drying to obtain acid-etched magnetic powder;
[0159] (4) In a hydrogen atmosphere, subjecting the acid-etched magnetic powder of step (3) to a second heat treatment at 800° C. for 3.5 h to complete shaping and obtain shaped magnetic powder.
[0160] Embodiment 22
[0161] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 21 except that the temperature of the second heat treatment in step (4) is 770°C.
[0162] Embodiment 23
[0163] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 21 except that the temperature of the second heat treatment in step (4) is 830°C.
[0164] Embodiment 24
[0165] This embodiment provides a method for shaping magnetic powder, which is the same as that of Embodiment 21 except that the atmosphere of the second heat treatment in step (4) is pure nitrogen.
[0166] Comparative Example 4
[0167] This comparative example provides a method for shaping magnetic powder, which is the same as Example 21 except that the second heat treatment in step (4) is not performed.
[0168] Comparative Example 5
[0169] This comparative example provides a method for shaping magnetic powder, which is the same as Example 21 except that the acid etching treatment of step (3) is performed first and then the ball milling treatment of step (2) is performed.
[0170] The magnetic powders obtained in Examples 21-24 and Comparative Examples 4-5 were surface passivated with phosphoric acid, and then the passivated magnetic powders were treated with a silane KH500 coupling agent, and then silicone resin was added. The powders were dried and granulated, and a zinc stearate release agent was added. The treated magnetic powders were placed in a mold with an outer diameter of 12.7 mm and an inner diameter of 7.6 mm for cold pressing at a pressure of 1700 MPa. The formed magnetic rings were placed in an annealing furnace for stress relief annealing in a nitrogen atmosphere at a temperature of 710°C for 2 hours to obtain a magnetic ring with a magnetic permeability of 60±3. The density, loss and DC superposition characteristics of the magnetic rings were tested.
[0171] The morphology and median particle size (D50) of the magnetic powders obtained in Examples 21-24 and Comparative Examples 4-5, as well as the density ρ, loss Pcv (50kHz, 100mT), magnetic permeability μ, and DC superposition characteristics (100Oe) DC-bias of the magnetic cores are shown in Table 5 below:
[0172] Table 5
[0173]
[0174]
[0175] It can be seen from Table 5 that the second heat treatment can improve the processing characteristics of the magnetic powder. The density of the magnetic core pressed by the treated magnetic powder is higher. At the same time, the insulation temperature and time of the heat treatment also have a certain influence on the molding density of the magnetic core, thereby affecting the magnetic properties of the magnetic core. In addition, the reducing atmosphere during the heat treatment process can effectively remove the oxygen introduced during the shaping process, thereby affecting the loss characteristics of the magnetic core; and, due to the coordination between the steps, the present invention preferably performs ball milling first and then acid etching.
[0176] In summary, the present invention provides a magnetic powder and a shaping method and application thereof, wherein the shaping method can effectively remove burrs and sharp corners caused by mechanical crushing of magnetic powder by improving the processing characteristics of magnetic powder, ball milling shaping and micro-repairing, and finally obtain magnetic powder with high sphericity, smooth surface and no sharp corners, thereby effectively improving the density, loss and DC superposition characteristics of the magnetic core.
[0177] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for shaping magnetic powder, characterized in that: The shaping method comprises the following steps: (1) subjecting the magnetic powder to a first heat treatment and ball milling in sequence to obtain ball-milled magnetic powder; (2) subjecting the ball-milled magnetic powder of step (1) to acid etching and a second heat treatment in sequence to complete shaping and obtain shaped magnetic powder.
2. The shaping method according to claim 1, characterized in that: Step (1) The temperature of the first heat treatment is 800-850° C. and the holding time is 2-4 hours; Preferably, the cooling rate of the first heat treatment in step (1) is 150-200°C / h, and the terminal temperature of the cooling is 20-35°C; Preferably, the first heat treatment in step (1) is carried out under vacuum conditions, or in a protective gas, wherein the protective gas comprises any one of hydrogen, nitrogen or argon, or a combination of at least two of them.
3. The shaping method according to claim 1 or 2, characterized in that: The magnetic powder in step (1) comprises mechanically crushed magnetic powder; Preferably, the magnetic powder in step (1) comprises mechanically crushed Sendust magnetic powder.
4. The shaping method according to any one of claims 1 to 3, characterized in that: In step (1), a grinding aid and grinding balls are added during the ball milling, and after the ball milling is completed, the grinding aid and grinding balls are removed to obtain ball-milled magnetic powder; Preferably, the method of removing the grinding aid comprises magnetic separation, and the method of removing the grinding balls comprises screening.
5. The shaping method according to claim 4, characterized in that: The grinding aid includes silicon dioxide; Preferably, the average particle size of the silicon dioxide is 1-4 μm, preferably 2-3 μm; Preferably, the amount of the grinding aid is 0.8-2 wt % of the weight of the magnetic powder after the first heat treatment.
6. The shaping method according to claim 4 or 5, characterized in that: The mass ratio of the grinding balls to the magnetic powder after the first heat treatment is (3-5):1; Preferably, the material of the grinding balls includes zirconium oxide; Preferably, the grinding balls include first grinding balls with a diameter of 0.5-1.5 mm and second grinding balls with a diameter of 2.5-3.5 mm; Preferably, the mass ratio of the first grinding balls to the second grinding balls is (1.5-3):
1.
7. The shaping method according to any one of claims 1 to 6, characterized in that: The mass concentration of the acid solution used in the acid etching in step (2) is 3.5-6.5%; Preferably, the acid etching time in step (2) is 10-30s; Preferably, the acid etching in step (2) is followed by cleaning and then a second heat treatment; Preferably, the cleaning solution used for cleaning includes distilled water and anhydrous ethanol; Preferably, the temperature of the second heat treatment in step (2) is 780-830° C., and the holding time is 3-5 h; Preferably, the second heat treatment in step (2) is performed in a reducing atmosphere, wherein the reducing atmosphere includes hydrogen and a mixed gas of hydrogen and nitrogen.
8. The shaping method according to any one of claims 1 to 7, characterized in that: The shaping method comprises the following steps: (1) subjecting the magnetic powder to a first heat treatment at a temperature of 800-850° C. for 2-4 hours under vacuum conditions or in a protective gas, and then cooling the temperature to 20-35° C. at a cooling rate of 150-200° C. / h to obtain magnetic powder after the first heat treatment; The magnetic powder includes mechanically crushed sendust magnetic powder, and the protective gas includes any one of hydrogen, nitrogen or argon, or a combination of at least two of them; (2) ball-milling the grinding aid, grinding balls and the magnetic powder after the first heat treatment in step (1), then removing the grinding aid by magnetic separation, and removing the grinding balls by screening to obtain ball-milled magnetic powder; The amount of the grinding aid is 0.8-2wt% of the weight of the magnetic powder after the first heat treatment, and the mass ratio of the grinding ball to the magnetic powder after the first heat treatment is (3-5):1; The grinding aid is silicon dioxide with an average particle size of 2-3 μm, the grinding balls include first grinding balls with a diameter of 0.5-1.5 mm and second grinding balls with a diameter of 2.5-3.5 mm, and the mass ratio of the first grinding balls to the second grinding balls is (1.5-3):1; (3) etching the ball-milled magnetic powder in step (2) in an acid solution having a mass concentration of 3.5-6.5% for 10-30 seconds, and then washing with distilled water and anhydrous ethanol to obtain acid-etched magnetic powder; (4) In a reducing atmosphere, subjecting the acid-etched magnetic powder of step (3) to a second heat treatment at a temperature of 780-830° C. for 3-5 hours to complete shaping and obtain shaped magnetic powder.
9. A magnetic powder, characterized in that: The magnetic powder is shaped by the shaping method according to any one of claims 1 to 8.
10. A magnetic core, characterized in that: The magnetic core includes the magnetic powder as claimed in claim 9.
Citation Information
Patent Citations
Preparing method for ball-like metal magnetically soft alloy powder
CN105710378A